Lectin Stimulation of Tissue Thromboplastin Activity in Human Monocytes in vitro - Lyberg, T; Prydz, H (Thrombosis and Haemostasis, 1979)
Lectins (phytohaemagglutinin, concanavalin A and wheat germ agglutinin) trigger an increase in tissue thromboplastin activity of human monocytes in vitro. The presence of serum was not necessary and did not enhance the activity. The increase was inhibited by cycloheximide and actinomycin D, suggesting that de novo protein synthesis is involved.